Numerical analysis of layered fiber composites accounting for the onset of delamination. (February 2015) - Simon, Jaan-Willem; Stier, Bertram; Reese, Stefanie
Abstract: Since delamination is a major failure mode of layered composites, predicting its initiation is essential for the design of composite structures. Evaluating delamination onset criteria based on stress–strength relations requires an accurate representation of the through-the-thickness stress distribution, which is delicate for thin shell-like structures. Therefore, in this paper, a solid-shell finite element is utilized, which allows for incorporating a fully three-dimensional, anisotropic, micro-mechanically motivated material model, still being suited for application to thin structures. Moreover, locking phenomena are cured by using both the enhanced assumed strain (EAS) and the assumed natural strain (ANS) concept, and numerical efficiency is ensured through reduced integration.